Indirect clinical markers for the detection of anabolic steroid abuse beyond the conventional doping control in athletes - Christou, G. A.; Christou, M. A.; Ziberna, L.; Christou, K. A. (European Journal of Sport Science, 2019)
Growing analytical challenges have arisen for the detection of misuse of androgenic anabolic steroids (AAS) in athletes the last years. Therefore, consideration of additional indirect markers can substantially aid the efforts to detect AAS abuse in athletes. Moreover, this approach can also help physicians to suspect AAS abuse when treating athletes. Laboratory markers highly indicative of AAS abuse in athletes include the considerable downregulation of high density lipoprotein-cholesterol, elevation of haematocrit or serum Gamma-glutamyl transpeptidase levels and for males reduced serum levels of both luteinizing hormone and follicle-stimulating hormone. Moreover, physical signs suggestive of current AAS abuse are hypertension, apparent changes in behaviour making the athlete more irritable and aggressive and the sudden appearance of acne vulgaris in an adult athlete with no recent history of acne, while testicular atrophy and gynecomastia raise suspicion of current or past AAS abuse in male athletes.